Wiskott Aldrich Syndrome: A Multi-Institutional Experience From India - Suri, Deepti; Rikhi, Rashmi; Jindal, Ankur K.; Rawat, Amit; Sudhakar, Murugan; Vignesh, Pandiarajan; Gupta, Anju; Kaur, Anit; Sharma, Jyoti; Ahluwalia, Jasmina; Bhatia, Prateek; Khadwal, Alka; et al. (Frontiers in Immunology, 2021)
Background: Wiskott Aldrich syndrome (WAS) is characterized by bleeding manifestations, recurrent infections, eczema, autoimmunity, and malignancy. Over the last decade, improved awareness and better in-house diagnostic facilities at several centres in India has resulted in increased recognition of WAS. This study reports collated data across major primary immunodeficiency diseases (PID) centres in India that are involved in care of children with WAS and highlights the varied clinical presentations, molecular profile, and outcomes of patients in India. Methods: Request to share data was sent to multiple centres in India that are involved in care and management of patients with PID. Six centres provided requisite data that were compiled and analyzed. Results: In this multi-institutional cohort, clinical details of 108 patients who had a provisional diagnosis of WAS were received. Of these, 95 patients with ‘definite WAS’ were included. Fourteen patients were classified as XLT and 81 patients as WAS. Median age at onset of symptoms of patients was 3 months (IQR 1.6, 6.0 months) and median age at diagnosis was 12 months (IQR 6,48 months). Clinical profile included bleeding episodes (92.6%), infections (84.2%), eczema (78.9%), various autoimmune manifestations (40%), and malignancy (2.1%). Molecular analysis revealed 47 variants in 67 cases. Nonsense and missense variants were the most common (28.4 % each), followed by small deletions (19.4%), and splice site defects (16.4%). We also report 24 novel variants, most of these being frameshift and nonsense mutations resulting in premature termination of protein synthesis. Prophylactic intravenous immunoglobulin (IVIg) was initiated in 52 patients (54.7%). Hematopoietic stem cell transplantation (HSCT) was carried out in 25 patients (26.3%). Of those transplanted, disease-free survival was seen in 15 patients (60%). Transplant related mortality was 36%. Outcome details were available for 89 patients. Of these, 37% had died till the time of this analysis. Median duration of follow-up was 36 months and total duration of follow-up was 217.8 patient-years. Conclusions: We report the first nationwide cohort of patients with WAS from India. Bleeding episodes and infections are common manifestations. Mortality continues to be high as curative therapy is not accessible to most of our patients.